Influence of launch beam distribution on power flow and angular division multiplexing in seven-core silica optical fibers - Savović, Svetislav; Dai, Wenjing; Djordjevich, Alexandar; Aidinis, Konstantinos; Li, Zheng; Min, Rui (Frontiers in Physics, 2022)
We analyze the effect of launch beam distribution on space-division multiplexing (SDM) performance in multimode multicore silica optical fibers (MM MC SOF) with seven cores. The time-independent power flow equation (TI PFE) is used to explore the effect of the width of the distribution of the Gaussian launch beam on power flow in each of the seven cores. We show that the optical fiber length at which the equilibrium mode distribution (EMD) and steady-state distribution (SSD) are obtained is greatly influenced by the width of the Gaussian launch beam distribution. We further show that when the width of the Gaussian launch beam distribution widens, the optical fiber length at which angular division multiplexing (ADM) in each of the seven cores can be realized with minimal crosstalk between neighboring angular optical channels decreases. We demonstrate that, for increasing the capacity of an optical fiber transmission system, an SDM system with two- and three-channel ADM and multicore optical fiber multiplexing can be implemented with the proposed seven-core MM MC SOF at optical fiber lengths up to 1 km (2 ADM channels x 7 cores) and x200 m (3 ADM channels x 7 cores), respectively. Such characterization of MM MC SOFs under various launch conditions is important for building a multicore optical fiber SDM transmission system.